What Doesn’t Work in the European Cohesion Policy? Development Challenges of the Inner Periphery After the SARS-CoV-2 Pandemic - Churski Paweł; Adamiak Czesław; Dubownik Anna; Pietrzykowski Maciej; Szyda Barbara (Quaestiones Geographicae)
The EU’s cohesion policy is a fundamental component of intervention policies in united Europe. Its primary goal is to reduce the scale of spatial differences in development by striving to improve economic, social, and territorial cohesion. The outcomes of the actions implemented to date have been unsatisfactory. This underperformance is the basis for the ongoing discussion in Europe about the future paradigm of post-2027 cohesion policy. This article systematises the challenges and proposes recommendations concerning the actions of EU cohesion policy that should be considered in the new paradigm of this public intervention, enhancing its effectiveness and efficiency during a period of strong pressure from external development shocks, especially in less-developed areas such as inner peripheries. Its unique value is constructed on two fundamental factors. Firstly, the presented results are the outcome of qualitative field research, providing unique empirically factual material. Secondly, they concern the processes occurring in relation to the territories of the member state that is the largest beneficiary of EU cohesion policy, Poland, which is often regarded as a specific laboratory for cohesion policy.